Annihilation of Extremely Halophilic Archaea in Hide Preservation Salt Using Alternating Electric Current - (:unkn) unknown (JOHNSON MATTHEY PUBL LTD CO, 2015)
Salt contains extremely halophilic archaea and these microorganisms degrade leather quality. The aim of this study is to find an effective treatment system to kill these microorganisms in salt used in hide brine curing. Ten salt samples were obtained from Tuz Lake, Turkey, and the total cell counts of extremely halophilic archaea, proteolytic and lipolytic extremely halophilic archaea were determined. Two sets of experiments were designed to detect the inactivation impact of alternating electric current on extremely halophilic archaea. In the first experiment, 2 A alternating electric current was applied for 25 min to the salt samples dissolved in liquid medium. In the second experiment, 2 A alternating electric current was applied for 25 min to the isolates of proteolytic extremely halophilic archaea, lipolytic extremely halophilic archaea, both proteolytic and lipolytic extremely halophilic archaea, and a mixed culture of these isolates. The extremely halophilic archaea in salt (10(2)-10(4) colony forming units (CFU) g(-1)) was annihilated in 1 min via alternating electric current and a 5 min treatment with the current was enough to destroy extremely halophilic archaeal isolates (106 CFU ml(-1)) obtained from salt samples. This electric treatment was found fairly effective to kill proteolytic and lipolytic extremely halophilic archaea in salt used for preservation of hide.
Keywords: GRAM-NEGATIVE BACTERIA; PACK CURED HIDES; ESCHERICHIA-COLI; MICROBIAL ECOLOGY; SOAK LIQUORS; TUZ LAKE; INACTIVATION; CELLS; MICROORGANISMS; DIVERSITY